TOR and SnRK1 signaling pathways in plant response to abiotic stresses: Do they always act according to the "yin-yang" model? - Rodriguez, Marianela; Parola, Rodrigo; Andreola, Sofia; Pereyra, Cintia; Martínez-Noël, Giselle (2020)
Plants are sessile photo-autotrophic organisms continuously exposed to a variety of environmental stresses. Monitoring the sugar level and energy status is essential, since this knowledge allows the integration of external and internal cues required for plant physiological and developmental plasticity. Most abiotic stresses induce severe metabolic alterations and entail a great energy cost, restricting plant growth and producing important crop losses. Therefore, balancing energy requirements with supplies is a major challenge for plants under unfavorable conditions. The conserved kinases target of rapamycin (TOR) and sucrose-non-fermenting-related protein kinase-1 (SnRK1) play central roles during plant growth and development, and in response to environmental stresses; these kinases affect cellular processes and metabolic reprogramming, which has physiological and phenotypic consequences. The "yin-yang" model postulates that TOR and SnRK1 act in opposite ways in the regulation of metabolic-driven processes. In this review, we describe and discuss the current knowledge about the complex and intricate regulation of TOR and SnRK1 under abiotic stresses. We especially focus on the physiological perspective that, under certain circumstances during the plant stress response, the TOR and SnRK1 kinases could be modulated differently from what is postulated by the "yin-yang" concept.